Multiple reports of adverse events related to an error of dose fractionation or session frequency in radiation therapy – Technical analysis. (December 2017) - Derreumaux, S.; Etard, C.
Abstract : Introduction: Between January 2013 and June 2015, 17 significant adverse events (SE) have been reported to the ASN (French Nuclear Safety Authority) regarding an error of dose fractionation or session frequency for the treatment of patients in external radiotherapy. The ASN asked the IRSN to conduct an analysis of the causes of these problems and make recommendations to users of the record and verify systems (R & V) and their suppliers. The ASN request covered technical, organizational and human aspects. Only the technical aspects are presented here. Methods: The IRSN analyzed the declaration forms and SE reports transmitted by the radiotherapy departments. A detailed survey was performed of reporting departments. An interview was held with each of the vendors of R & V systems, followed by a visit in radiotherapy departments using the latest versions of these systems. Then, a comprehensive study was conducted on technical aspects in the design and use of software managing parameters of irradiation, especially R & V systems, which evolved into information in radiation therapy systems (IRTS). Results: The 17 SE concern treatments with non-specialized devices. Eleven SE concern an error of dose fractionation, most of the time associated with a problem of session frequency. Ten of these SE were initially caused by an error during treatment planning, with an erroneous transcription of the prescription in the TPS. Automatic detection by the SIRT was held for only 2 SE, and only at the end of treatment. For 2 SE, the total delivered dose was much higher than the prescribed dose (+50% and +20%). In both cases, the technique of treatment was an intensity modulation technique and software were MOSAIQ® and PINNACLE, generating a particular risk that was parsed. Six SE concern a session frequency error. Most of these SE were initially caused by an error when programming the planned dates of treatment sessions. Detection of the error was always human, during the treatment. Most of the SE concerns a fractionation or frequency non-standard protocol. The latest versions of ARIA® and MOSAIQ® offer several management features of fractionation or frequency, with defense barriers and failures that are common or specific to the software. Conclusions: The IRSN published on its website a notice with its recommendations on the design and use of the software, particularly the R & V/SIRT.